Por trás das câmeras: diretoras e diretores negros e o fazer cinema no Brasil - Rodrigues, Ana Ligia Muniz (2019)
This paper analyzes the cinematographic activity of black filmmakers in Brazil. Considering the racial tensions that mark Brazilian society and the whitening pattern present in the national audiovisual, the objective was to understand the social context in which these filmmakers produce their films. The research investigates how the social marker of race interferes in the behind-the-camera dynamics and defines the place of black directors in the Brazilian cinematographic environment. However, interviews and a documentary analysis of the reports of directors Joelzito Araújo, Adélia Sampaio, Jeferson De and Yasmin Thayná were carried out. Thus, it was possible to observe the transformations that have taken place in the debate about race in Brazil over the years, federal public policies focusing on black filmmakers, and the changes inherent in the field of cinema. The investigated trajectories indicate that, despite the racist structures that mark the formation of Brazil, these filmmakers mobilize different types of resources and found a dimension of agency to work in their professions.